Molecular Testing for Oncogenic Gene Alterations in Pediatric Thyroid Lesions - Mostoufi-Moab, Sogol (Thyroid, 2018)
Background: Thyroid nodules are less common in pediatric patients (i.e., those ≤18 years) than they are in adults. The Bethesda System for Reporting Thyroid Cytopathology allows for individual risk stratification, but a significant number of nodules are indeterminate. Incorporating gene mutation panels and gene expression classifiers may aid in preoperative diagnosis. The overall aim of this study was to assess the prevalence of oncogene alterations in a representative pediatric population and across a broad-spectrum of thyroid tumor diagnoses. Methods: This was a retrospective cross-sectional evaluation of 115 archived samples, including: 47 benign (29 follicular adenoma, 11 diffuse hyperplasia, four thyroiditis, and three multinodular goiter), six follicular thyroid carcinomas (FTC), 24 follicular variant of papillary thyroid carcinomas (fvPTC), 27 classic variant of PTC (cPTC), eight diffuse sclerosing variant of PTC (dsvPTC), and three other PTC. Molecular testing was performed by multiplex qualitative polymerase chain reaction followed by bead array cytometry. Oncogene results were analyzed for association with age, sex, histology, lymph node metastasis, and intrathyroidal spread. Results: A mutation in one of the 17 molecular markers evaluated was found in: 2/6 (33%) FTC, 8/24 (33%) fvPTC, 17/27 (63%) cPTC, and 4/8 (50%) dsvPTC. Mutations in RAS or PAX8/PPARG were exclusive to FTC and fvPTC. BRAF was the most common mutation in cPTC (12/17; 71%), and RET/PTC was the only mutation associated with dsvPTC. Overall, a mutation was found in 32/68 (47%) malignant specimens, with a single follicular adenoma positive for PAX8/PPARG. The relative distribution of gene alterations in pediatric lesions was similar to adults. The presence of a BRAF mutation in pediatric cPTC did not predict a more invasive phenotype. Conclusions: Of 33 nodules with genetic alterations, 32 were malignant. Mutations in RAS were most frequently associated with FTC, RET/PTC rearrangements with dsvPTC, and invasive fvPTC, and BRAF with cPTC. These results suggest a clinical role for mutational analysis of pediatric nodules to guide the surgical approach.